Impact of Financial Literacy and Attitudes on FEB Untan Students' Financial Management Behavior - Dio, Louisio; Listiana, Erna; Syahputri, Anggraini; Giriati; Azazi, Anwar (MultiTech Publisher, 2025)
Attitudes and financial literacy are increasingly recognized as pivotal factors in shaping responsible financial management behavior among university students. In today’s complex financial environment, where digital transactions and consumer credit are more accessible than ever, equipping students with the right knowledge and mindset has become essential (Lusardi & Mitchell, 2020; OECD, 2023). This study explores the influence of financial literacy and financial attitudes on students' financial behavior, focusing on 217 students from the Economic Education program at FEB Untan, selected through purposive sampling. Data were analyzed using SPSS to ensure statistical reliability. The results indicate that students with higher levels of financial knowledge and more positive financial attitudes demonstrate better financial management practices. Their ability to make informed decisions, budget effectively, and avoid impulsive spending reflects the integration of financial understanding into everyday behavior. These findings underscore the importance of enhancing financial literacy and fostering positive financial attitudes to better prepare students for navigating increasing financial complexities and achieving long-term financial well-being